Time Use and Macroeconomic Uncertainty - Cacciatore, Matteo; Gnocchi, Stefano; Hauser, Daniela (The Review of Economics and Statistics, 2024)
Abstract We study the effects of uncertainty on time use and their macroeconomic implications. Employing data from the American Time Use Survey and the Bureau of Labor Statistics, we document that heightened uncertainty increases housework and reduces market hours, mildly impacting leisure. We then propose a model that quantitatively accounts for these estimates. We show that substitution between market and housework provides self-insurance to households, weakening precautionary motives. However, it also reduces aggregate demand, ultimately amplifying uncertainty's recessionary impact. Time reallocation can lead to higher inflation, particularly when uncertainty is coupled with policies redirecting time use towards housework (e.g., lockdown restrictions).